P2P Research and Reality: Some Preliminary Thoughts - Zhang, Zheng (Institute of Electrical and Electronics Engineers, Inc., 2004)
In this paper, we start by recounting some of the myth and truth of P2P systems. Getting a good understanding of those issues are good starting points. Even more important will be performing researches that understand the fundamental properties, and that actually build the environment and forester the creativition of new applications.